Analisis Keamanan pada Aplikasi Her-registrasi Online Mahasiswa Universitas Diponegoro - Hilal Afrih Juhad; R. Rizal Isnanto; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
The security aspect is often forgotten in the application of Information Technology. The attacks were caused by the negligence of the developer causes damage to the system used. SQL Injection attacks, Cross Site Scripting attacks, and no use of encrypted channels lead to the exposure of sensitive data users. Objectives of this research is to perform an audit and analysis of the security aspects against the Her-registration Colege Students Online Application of Diponegoro University. Audit and security analysis is prevention step so that the vulnerabilities found not to be a entrances to the system hackers. The results of this research are a security audit report that contains the vulnerability Her-registration College Students Online Application of Diponegoro University. The audit report will be used as a reference for application developers Her-registration Colege Students Online Application of Diponegoro University to improve the system.